Impact of renal function variability on long-term prognosis in ischemic stroke patients with atrial fibrillation - Wang, Xiao; Sin, Chun-fung; Teo, Kay-Cheong; Leung, William C. Y.; Wong, Yuen-Kwun; Liu, Roxanna K. C.; Fok, Joshua W.; Ip, Bonaventure Y.; Kwan, Hon Hang; Lee, Tsz Ching; Sheng, Bun; Yip, Edwin Kin-Keung; et al. (Frontiers in Neurology, 2024)
Background Although renal dysfunction is associated with adverse clinical outcomes in patients with atrial fibrillation (AF) following stroke, the impact of renal function variability is unclear. Aim This study aimed to assess the association between renal function variability and various adverse clinical outcomes in patients with transient ischemic attack (TIA)/ischemic stroke and atrial fibrillation (AF). Methods We conducted a population-based study and retrospectively identified patients hospitalized with a diagnosis of TIA/ischemic stroke and AF during 2016–2020 using the Clinical Data Analysis and Reporting System of Hong Kong. Serial serum creatinine tested upon the onset of TIA/ischemic stroke and during their subsequent follow-up was collected. Renal function variability was calculated using the coefficient of variation of the estimated glomerular filtration rate (eGFR). Clinical endpoints that occurred during the study period were captured and included ischemic stroke/systemic embolism, intracerebral hemorrhage (ICH), total bleeding, major adverse cardiovascular events (MACE), cardiovascular, non-cardiovascular, and all-cause mortality. Competing risk regression and Cox proportional hazard regression models were used to assess the associations of renal function variability with the outcomes of interest. Results A total of 3,809 patients (mean age 80 ± 10 years, 43% men) who satisfied the inclusion and exclusion criteria were followed up for a mean of 2.5 ± 1.5 years (9,523 patient-years). The mean eGFR was 66 ± 22 mL/min/1.73 m2 at baseline, and the median number of renal function tests per patient during the follow-up period was 20 (interquartile range 11–35). After accounting for potential confounders, a greater eGFR variability was associated with increased risks of recurrent ischemic stroke/systemic embolism [fully adjusted subdistribution hazard ratio 1.11, 95% confidence interval (CI) 1.03–1.20], ICH (1.17, 1.01–1.36), total bleeding (1.13, 1.06–1.21), MACE (1.22, 1.15–1.30), cardiovascular (1.49, 1.32–1.69), non-cardiovascular (1.43, 1.35–1.52), and all-cause mortality (fully adjusted hazard ratio 1.44, 1.39–1.50). Conclusion Visit-to-visit renal function variability is independently associated with adverse clinical outcomes in TIA/ischemic stroke patients with AF. Further large-scale studies are needed to validate our results.